Strategy as practice: an organizational culture approach in a higher education institution in Kosovo - Berisha, Hajdin; Mustafa, Saxhide; Ismail, Yusof (Sciendo DeGruyter, 2018)
Organizational members perceive top management as the sole authority for strategy making. Whilst this has been true for a number of years, the last decade has provided a shift to this traditional strategy practice in some sectors in the society. This paper attempts to address two major questions: firstly, whether the classical view of strategy as a property of organizations and the sole responsibility of top management in strategy making holds true in one of the higher education institutions in Kosovo as a member of western Balkan and eastern European countries. Secondly, how top management influences strategy practices of sense-making and sense-giving through organizational culture. The research analyses organizational culture and its effect on strategy as practice before and after a shift of institution’s top management based on its six strategy dimensions. The study employs multiple sources of data to address the research questions: secondary sources, semi-structured interviews, informal discussions with institution’s staff members, two-week of shadowing, observations and viewing artefacts of the institution. Results reveal three threads: organizational culture plays an important role on strategy as practice; top management is perceived to primarily provide sense through face-to-face interaction and procedural measures of strategy practices; and staff members are mostly involved in implementation. Moreover, clan and hierarchical types of organizational culture are identified to shape strategy practices of the institution. The study suggests that while the strategy making practice should be at the core of institution, a pleasant and non-confronting organizational culture is crucial to attract new students and retain elite staff.